Determinants Affecting Participants' Decision-Making In Convention Tourism In Sarawak - Chuah, Henry Kun Liang (Universiti Malaysia Sarawak, (UNIMAS), 2016)
This study aims to investigate the determinants that are affecting the convention attendees' participation decision-making in Kuching, Sarawak. The data was obtained through a set of close-ended questionnaires and collected from 142 respondents through the convention held in Kuching. The questionnaires consist of four determinants that belief to be influencing the convention attendees' participation decision-making; Association/Conference Factors, Location Factors, Total Cost Factors, and Personal Factors. The data were analyzed using descriptive statistic, Pearson's correlation coefficient, and multiple regression analysis. The results showed that the Location Factors and Total Cost Factors are significant relationship with convention attendees' participation decision-making. This research suggests that the event planner should look into the two determinants that has significance relationship to attract more attendees to the convention. A guidance for future research studies were provided.